The Effect of Leverage, Sales Growth, and Growth Opportunity on Financial Performance in the Property Sector Listed on the Indonesia Stock Exchange in 2021–2025 - Insan Alfaqih; Surono; Muzayanah (Citakonsultindo, 2026)
Financial performance is an important indicator in assessing a company's ability to generate profits, manage resources, and maintain business sustainability. In property sector companies, financial performance is influenced by various factors, such as leverage, sales growth, and growth opportunities, which reflect the effectiveness of the capital structure, sales growth, and the company's development prospects. This study aims to analyze the influence of Leverage, Sales growth, and Growth opportunity on financial performance in property sector companies listed on the Indonesia Stock Exchange for the 2021–2025 period. The research uses a quantitative approach with an associative research design. The data used is in the form of secondary data obtained from the company's annual financial statements. The research sample was determined using purposive sampling techniques, so that 50 companies were obtained with 250 observation data over five years. Data analysis was carried out using multiple linear regression with the help of IBM SPSS Statistics, through classical assumption tests, partial tests (t), simultaneous tests (F), and determination coefficient tests (R²). The results of the study showed that Leverage had a positive and significant effect on financial performance with a value of t = 2.513 and sig. = 0.015, Sales growth has a positive and significant effect with a value of t = 3.021 and sig. = 0.002, and Growth opportunity has a positive and significant effect with a value of t = 2.625 and sig. = 0.011. Simultaneously, the three variables had a significant effect on financial performance with values F = 40.163 and sig. = 0.000. The R-Square value of 0.507 indicates that 50.7% of the variation in financial performance can be explained by all three independent variables, while 49.3% is influenced by other factors outside the research model. These findings show that managing capital structures, increasing sales growth, and optimizing growth opportunities play an important role in improving the financial performance of companies in the property sector.